2016
DOI: 10.18632/oncotarget.11992
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA/Runx1/Runx2 network regulates prostate tumor progression from onset to adenocarcinoma in TRAMP mice

Abstract: While decades of research have identified molecular pathways inducing and promoting stages of prostate cancer malignancy, studies addressing dynamic changes of cancer-related regulatory factors in a prostate tumor progression model are limited. Using the TRAMP mouse model of human prostate cancer, we address mechanisms of deregulation for the cancer-associated transcription factors, Runx1 and Runx2 by identifying microRNAs with reciprocal expression changes at six time points during 33 weeks of tumorigenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
0
17
1
Order By: Relevance
“…The goal of our study was to identify if RUNX1 plays a clinically important role in lung adenocarcinoma and lay the foundation for valuable translational investigation. While loss of RUNX1 has been associated with breast (Hong et al, ; Janes, ) and prostate (Farina et al, ; Takayama et al, ) cancers, our findings in lung have identified a key role for RUNX1 not previously reported in lung cancer. We show the loss of RUNX1 is a driver of aggressiveness and prognosis in lung adenocarcinoma, phenotypes that may be mediated through E2F1 pathways that support proliferation.…”
Section: Discussioncontrasting
confidence: 54%
“…The goal of our study was to identify if RUNX1 plays a clinically important role in lung adenocarcinoma and lay the foundation for valuable translational investigation. While loss of RUNX1 has been associated with breast (Hong et al, ; Janes, ) and prostate (Farina et al, ; Takayama et al, ) cancers, our findings in lung have identified a key role for RUNX1 not previously reported in lung cancer. We show the loss of RUNX1 is a driver of aggressiveness and prognosis in lung adenocarcinoma, phenotypes that may be mediated through E2F1 pathways that support proliferation.…”
Section: Discussioncontrasting
confidence: 54%
“…In spite of the significant upregulation of miR-375 in the serum of castration-resistant PCa patients [48] , we observed a significant reduction of miR-375-3p with tricirbine treatment in the advanced tumor-bearing TRAMP mice. Interestingly, during their investigation for the miRNA-Runx1/2 signaling network in the regulation of PCa progression in TRAMP mice and by looking at the temporal miRNAs expression in TRMAP's tumors, Farina et al have also noticed a significant reduction in miR-375-3p expression as the tumor develops in these mice compared to wild-type controls [49] . Although its expression was measured up to 21-week-old mice, the expression of Runx1/2, which are targets for miR-375-3p, was elevated in 33week-old TRAMPs indicating the potential reduction of miR-375-3p during that stage.…”
Section: Discussionmentioning
confidence: 99%
“…miR-384 has suppressive effects on tumor cell proliferation through the direct inhibition of IRS1 expression (Lai et al, 2016), and contributes to aberrant Runx expression in prostate tumors (Farina et al, 2016). In addition, several studies have demonstrated a relationship between miR-384 and the CNS.…”
Section: Discussionmentioning
confidence: 99%